Sistem Informasi Penilaian Kinerja Sales Lapangan dengan Metode Simple Additive Weighting (SAW) dan 360º - Fresa Dwi Juniar Sofalina; Asmui Mansur (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
PT. MGT BANDUNG is a leading company in the marketing and distribution of Japanese food, Western and local food products in Indonesia. In evaluating performance at PT. MGT BANDUNG there are no systems and methods applied, this makes it difficult for companies to make measurable assessments.Therefore the company needs to build an employee performance appraisal information system to assist in conducting a systematic performance appraisal and applying methods so that the calculations can be more accurate and measured. With the employee performance appraisal system in this case the Field Sales Division, an analysis and design of a performance appraisal information system was carried out with the 360º method and Simple Additive Weighting (Saw). The system design method uses tools namely UML (Unified Modeling Language), Use case diagrams, activity diagrams, Class diagrams, and Sequence Diagrams. As well as applications used in making desktop-based systems. The programming language used is VB.NET and the SqlServer programming language. The results achieved in this paper are an information system to assess the performance of field sales at PT. MGT BANDUNG. From the results of the application of performance evaluation information systems in the field sales division with the Simple Additive Weighting (Saw) method and 360º method at PT. MGT BANDUNG management is easier to determine the performance appraisal of each employee with more accurate calculations. By using an alternative weighting C1 30%, C2 50%, and C3 20%.